Fracture fixation in polytraumatized patients—From an interdisciplinary early total/appropriate care to the safe definitive surgery concept - Kalbas, Yannik; Heining, Sandro-Michael; Kaiser, Anne; Klingebiel, Felix Karl-Ludwig; Pfeifer, Roman; Wanner, Guido A.; Pape, Hans-Christoph (Frontiers in Medicine, 2024)
The strategies for the timing of fracture fixation in polytrauma patients have changed with improvements in resuscitation and patient assessment. Specifically, the criteria for damage control have been formulated, and more precise parameters have been found to determine those patients who can safely undergo primary definitive fixation of major fractures. Our current recommendations are supported by objective and data-based criteria and development groups. Those were validated and compared to existing scores. This review article introduces the concept of “safe definitive surgery” and provides an update on the parameters used to clear patients for timely fixation of major fractures.